Application of Good Corporate Governance Principles and Their Impact on the Performance of the Surabaya City Fire and Rescue Service - Ali Wafa; Ika Devy Pramudiana; Dian Ferriswara (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to describe and analyze: the implementation of Good Corporate Governance and how it affects the performance of the Surabaya City Fire and Rescue Service. The type of research used is qualitative research. The data analysis technique in the study uses a technique developed by McNabb (2002), namely Grouping the data according to key constructs, identifying bases for interpretation, developing generalizations from the data, Testing Alternative interpretations and forming and/or refining generalizable theory from case study. The results of the study show that in principle, the implementation of Good Corporate Governance (GCG) at the Surabaya Fire and Rescue Service (Dinas Pemadam Kebakaran Dan Penyelematan - DPKP) has been running well. In terms of administrative transparency, the availability of service information is substantially adequate and the media of its presentation, the certainty of service time and the available service complaint mechanism. Legal accountability and honesty at the Surabaya City Fire and Rescue Service are good. The Surabaya City Fire and Rescue Service is responsible for carrying out fire and disaster handling tasks. The 7-Minute Time Responsibility implemented by the Surabaya Fire and Rescue Service (DPKP) not only prioritizes response speed in extinguishing fires, but also respects the safety and welfare of all residents. The professionalism of service at the Surabaya City Fire and Rescue Service is shown through service innovation and fire handling. The